Transitivity in Pope Francis’ Speech in Morocco: A Systemic Functional Linguistic Analysis - EL Hadifi, Mohammed (Integrated Journal for Research in Arts and Humanities, 2023)
The way we speak and the words we choose to convey a certain message are not neutral. They are overloaded with certain meanings that represent our worldview, namely when delivered by most influential people like religious leaders and used in contexts which are ideologically constructed like that of the speech of Pope Francis with his symbolic power and role in religious diplomacy. The main aim of this study is to investigate the construction of experiential meanings in Pope Francis' historical speech during his apostolic journey to Morocco on March 19, 2019, by examining the specific linguistic choices employed. This study employs the transitivity model within the framework of systemic functional linguistics (SFL) as its theoretical foundation for analysis. Precisely, using quantitative analysis, this paper endeavors to address two key questions: Firstly, what distributions and patterns of transitivity has Pope Francis utilized in constructing experiential meanings in his speech in Morocco? Second, what functions do the transitivity processes and each participant involved have in the delivered speech text, aiding the speaker in conveying their intention? The dataset comprises 182 clauses extracted from the aforementioned speech. The results of this study showed that Pope Francis employed six types of transitivity processes, totaling 186 processes. Yet, material processes, constituting 62%, and mental processes, comprising 15%, were identified as dominant, suggesting their significant roles in conveying vibrant information in his speech that aimed to enhance dialogue and foster friendly relations between Catholicism and Islam, promoting cooperation in the construction and establishment of a world characterized by sincere, courageous, and essential collaboration. The findings therefore indicate that transitivity choices play a crucial role in conveying implicit meanings.